Pre-stack depth migration seismic imaging of the Coral Patch Ridge and adjacent Horseshoe and Seine Abyssal Plains (Gulf of Cadiz): tectonic implications - Martínez-Loriente, S.; Gràcia, E.; Bartolomé, R.; Klaeschen, D.; Vizcaino, A.; Sallarès, V.; Dañobeitia, J.; Zitellini, N. (TRABAJOS DE GEOLOGÍA, 2024)
Recently acquired multichannel seismic (MCS) profiles during the SWIM-2006 cruise allowus to characterize the shallow and deep geometry and timing of deformation of the structures comprisingthe Coral Patch Ridge and adjacent Horseshoe and Seine Abyssal Plains (SAP), at the westernmostGulf of Cadiz. This region is where the epicentres of the largest instrumental earthquakes occurred,such as the one on 28th February 1969 (Mw 8.0). We present a detailed seismo-stratigraphic and tectonicinterpretation of two SWIM-2006 MCS profiles that we have pre-stack depth migrated in orderto correct the reflectors geometry. Based on drilled wells, we have distinguished six seismo-stratigraphicalunits (from Triassic to Plio-Quaternary). We have also characterized the 300 km long WNW-ESElineaments, corresponding to an active dextral strike-slip fault, and the geometry of the Coral PatchRidge. Finally, present-day active faulting has been observed at the Horseshoe Abyssal Plain and SAP,mainly corresponding to subvertical faults cutting the whole sedimentary sequences up to the surface,some of them associated with earthquake swarms.